Kepemimpinan Transformasional dalam Lembaga Pendidikan - Didi Kriswanto (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2023)
The purpose of this writing is to describe transformational leadership in educational institutions. This research uses the method of literature study or library research. Articles that meet the criteria were published from 2016-2022, while the criteria for books were printed in 2006-2022. The results of the study show several findings, namely the dimensions of transformational leadership include: Idealized Influence, Individualized consideration, Intellectual stimulation, and Inspirational motivation. Then, transformational leadership in education has several characteristics, namely 1) visionary and always appears as a pioneer agent of change; 2) dare to make decisions prioritizing the interests of the institution over personal interests; 3) increases the sense of trust and mutual awareness; 4) give a positive influence on the relationship between superiors and subordinates; and 5) mobilizing subordinates to be actively involved in the change process. Furthermore, transformational leadership in educational institutions has principles that are in line with the leadership of Indonesian educational figures, namely Ki Hajar Dewantoro, who is known by the motto